Urine tenofovir concentrations correlate with plasma and relate to tenofovir disoproxil fumarate adherence: A randomized, directly observed pharmacokinetic trial (target study) - Paul K. Drain (2020)
© The Author(s) 2019. Background. Direct measurement of tenofovir (TFV) in urine could be an objective measure to monitor adherence to preexposure prophylaxis (PrEP) or TFV-based antiretroviral therapy (ART). Methods. We conducted a 3-arm randomized, pharmacokinetic study of tenofovir disoproxil fumarate (TDF) 300 mg/ emtricitabine (FTC) 200 mg among adults living with human immunodeficiency virus. Participants were randomized to receive controlled TDF/FTC dosing as (1) "perfect"adherence (daily); (2) "moderate"adherence (4 doses/week); or (3) "low"adherence (2 doses/week). We obtained trough spot urine and plasma samples during a 6-week directly observed therapy period and a 4-week washout period. TFV concentrations were compared between adherence arms using 1-way analysis of variance. Results. Among 28 participants, the median age was 33 years and 16 (57%) were male. Correlation between TFV plasma and urine concentrations was strong (p = 0.78; P < .0001). Median (interquartile range) steady-state trough TFV concentrations (ng/mL) for perfect, moderate, and low TDF adherence were 41 (26-52), 16 (14-19), and 4 (3-5) in plasma; and 6480 (3940-14 300), 3405 (2210-5020), and 448 (228-675) in urine. Trough TFV concentrations at steady state were significantly different between the 3 adherence arms for plasma (P < .0001) and urine (P = .0002). Following drug cessation, TFV concentrations persisted longer in urine than plasma samples. Washout urine TFV concentrations and time to undetectable concentrations did not differ between the 3 randomized adherence groups. Conclusions. Urine TFV concentrations can inform interpretation of novel point-of-care urine-based TFV assays to assess recent TDF adherence.